The Impact of Performance and CSR Assurance on Investment Decision Making - nial, Hawariah Dal; Azmi , Anna; Zakaria, Zarina (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates the impact of performance as well as independent corporate social responsibility (CSR) assurance in making an investment decision and how investors perceive both factors when deciding on the investment amount allocation by using 2 x 2 factorial between-subjects design with individual investors as the participants. This has provided valuable outcomes on the effect of the Performance and CSR assurance on investment decision making specifically for Malaysian investors. Findings show both Performance and CSR Assurance influenced investment amount allocation and the absence or presence of the CSR assurance report is important in the investment decision as well as to determine whether a company is performing well or otherwise. By controlling the Performance factor, the influence of CSR assurance could be observed. Results have empirically informed that CSR assurance seemed to only reaffirm investor decision making, explaining the absence of any difference when it was present. Nonetheless, without CSR assurance, the investment was significantly devalued by investors. This offers a better understanding of the impact of CSR assurance in a specific performance condition as individual investors value CSR assurance differently based on whether the company is performing well or poorly.